The Truth About Denial Bias and Self-Deception in Science, Politics, and Religion - Bardon, Adrian (Oxford University Press, 2019)
It is a striking-yet all too familiar-fact about human beings that our belief-forming processes can be so distorted by fears, desires, and prejudices that an otherwise sensible person may sincerely uphold false claims about the world in the face of overwhelming evidence to the contrary. When we describe someone as being "in denial," we mean that he or she is personally, emotionally threatened by some situation-and consequently has failed to assess the situation properly according to the evidence. People in denial engage in motivated reasoning about their situation: They (sincerely) argue and interpret evidence in light of a preestablished conclusion. One significant type of reason-distorting emotional threat is a threat to one's ideological worldview. When group interests, creeds, or dogmas are threatened by unwelcome factual information, biased thinking becomes ideological denialism. (One critical example of such denialism is the widespread denial of settled climate science.) Denial can stand in the way of individual well-being, and ideological denialism can stand in the way of good public policy. This book is a wide-ranging examination of denial and denialism. It offers a readable overview of the social psychology of denial, and examines the role of ideological denialism in conflicts over public policy, politics, and culture. Chapters focus on our philosophical and scientific understanding of denial, denial of scientific consensus, denialism in political economy, and denialism in religious belief. An afterword examines proposals for improving science communication in light of findings about motivated reasoning and denial.